Investigation of PFC on tapped-source AC/DC converter - Thet, Mon Sann. (2009)
The AC/ DC converter produces a dc output from an ac input. Average power is transferred from an ac source to a dc load. The ac-dc converter is specifically classified as a rectifier. For example, an AC/ DC converter enables integrated circuits to operate from a 60Hz ac line voltage by converting the ac signal to a dc signal of the appropriate voltage.